Giant condyloma acuminatum: report of surgical treatment and evolution of healing - Costa, Mariana Takahashi Ferreira; Gomes, Aline da Silva; Santos, Poliana Brito dos; Moura, Sara Ribeiro; Martins, Renata Soares; Scota, Sayonara; Oliveira, Andreia Cristine Deneluz Schunck de; Gamba, Mônica Antar; Nadal, Sidney Roberto (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Giant condyloma acuminatum, a rare variant of anogenital condyloma, shows rapid growth associated with immunodeficiency. Wound care after resection and outcomes were reported. NGS, black, 55 years, HIV positive, with giant condyloma acuminatum affecting from the groin to the intergluteal groove, which was resected, remaining the wound opened for later skin graft. Topical care included polihexametilene biguanide/betaine solution, essencial fatty acids solution, hydrofiber/silver, and poliuretane film. The wound developed secondary infection, so hidrofiber was replaced by polyurethane foam/silver/ibuprofen. There was improvement in infection and pain, contraction of the edges and the presence of granulation tissue across the lesion. In those conditions the skin graft was performed after 41 days. Despite possible confusion bias, it can be inferred that the care adopted prepared the wound bed to receive the skin graft.